PERNIKAHAN DENGAN WALI MUHAKKAM (STUDI TENTANG IMPLIKASI DAN PERSEPSI ULAMA DI KOTA BANJARMASIN) - SYUKUR, ABDUL KADIR (Universitas Islam Negeri Antasari Banjarmasin, 2014)
Marriage ideally using guardian nasab who still have blood relations with the bride. But there are many obstacles that cause the marriage cannot use the guardian nasab. In that situation, the guardian is replaced by the magistrate guardian. But some people want to take the easy path by treat Ulema, religious teacher, or certain figure as guardian Muhakkam. Basically, they are not entitled to be the marriage guardian, but this marriage practices are still occured, including in Banjarmasin. Is paper examines the issues of guardian nasab and muhakkam in the marriage. This paper results indicate that the reasons of using guardian muhakkam in marriage are because of the reluctance to deal with magistrate guardian and the desire to take the easy path in marriage. In the opinion of Ulama, that marriage is not valid because there is still a magistrate guardian authorized. Besides, that marriage causes a lot of disadvantage, especially for the wife. It is because the absence of legal force (marriage certificate), the difficulty to sue the rights of wife and child, and the difficulty to have a birth certificate.